THE ROLE OF EDUCATORS IN DEVELOPING SOCIO-CULTURAL CHARACTER IN LOCAL WISDOM-BASED LEARNING - Siti Fatmah Hiola; Abd. Muis (Adisam Publisher, 2025)
This research aims to examine the role of educators in fostering students' socio-cultural character through local wisdom-based learning. The study was conducted using a literature review approach on various relevant scientific sources, including journals, books, and research reports that discuss the integration of local values in character education. The study results indicate that educators have a strategic role as agents of cultural value transformation in the learning process. Through contextual, project-based, and culture-based learning models, teachers can internalize values such as mutual cooperation, tolerance, and social responsibility to students. Learning practices that utilize folk tales, traditional songs, and local traditions have proven effective in strengthening students' cultural identity and shaping positive social behavior in the school and community environment. This research emphasizes the importance of educator training, policy support, and community involvement in developing character education that is contextual and rooted in local culture.